Evaluation of the Importance of Patient Education in Peritoneal Dialysis - Meltem Gürsu; Derya Topçuoğlu; Nurcan Torun (Haseki Tıp Bülteni, 2010)
Aim: Peritoneal dialysis is the type of renal replacement therapy which requires active participation of the patient; therefore, the education of the patient is of major importance. We aimed to evaluate objectively the importance of continuation of education in patients on peritoneal dialysis (PD). Methods: Thirty patients included in our study were asked to perform two questionnaires before and after an education session lasting about 45 minutes. The questions were about the functions of the kidneys, renal failure and PD techniques in the first one, and peritonitis, hypervolemia and nutrition in the second questionnaire. The numbers of correct answers before and after the education were compared. Results: The mean number of correct answers raised from 5.48±1.7 to 6.26±1.6 with the education in the first (p=0.002) and from 5.14±1.5 to 7.14±0.9 in the second questionnaire (p<0.001). Although there was a significant improvement with education, it was more obvious in the second questionnaire, suggesting better performance of both the teaching nurses and patients. In the first questionnaire, fifteen patients’ results improved with the education, while correct answers did not change in six of them. The number of correct answers increased in nineteen patients, while in three of them it did not change in the second questionnaire. Conclusion: The success rate of about only 60% in a test performed during the following months of treatment, in spite of a dense education program at the beginning of the dialysis, shows that this education must be repeated regularly. (The Medical Bulletin of Haseki 2010; 48: 14-7)